Business Administration A2 learner’s Perceptions About The Use Of Cognitive Reading Strategies For Improving Reading Comprehension - Espol (2017)
The aim of the present study was to develop a lesson plan with reading activities which promote the use of cognitive reading strategies that enhance learners reading comprehension skills. According to oxford (1990), cognitive strategies are the most used strategies with language learners which help them to increase their reading comprehension. In total 50 female and male students with an a2 proficiency level acted as participants from a business dministration faculty of an ecuadorian public university. The study employed an action research design with quantitative and qualitative techniques. Researchers used a cloze test as a quantitative technique for the purpose of evaluating students’ progress in the reading process before and after the cognitive strategy training. Also, they applied a think aloud-protocol and a semi-structured interview as qualitative techniques.